Circular RNA expression is abundant and correlated to aggressiveness in early-stage bladder cancer. (December 2017) - Okholm, Trine; Nielsen, Morten; Hamilton, Mark; Christensen, Lise-Lotte; Vang, Søren; Hedegaard, Jakob; Hansen, Thomas; Kjems, Jørgen; Dyrskjøt, Lars; Pedersen, Jakob
Abstract The functions and biomarker potential of circular RNAs (circRNAs) in various cancer types are a rising field of study, as emerging evidence relates circRNAs to tumorigenesis. Here, we profiled the expression of circRNAs in 457 tumors from patients with non-muscle-invasive bladder cancer (NMIBC). We show that a set of highly expressed circRNAs have conserved core splice sites, are associated with Alu repeats, and enriched with Synonymous Constraint Elements as well as microRNA target sites. We identified 113 abundant circRNAs that are differentially expressed between high and low-risk tumor subtypes. Analysis of progression-free survival revealed 13 circRNAs, among them circHIPK3 and circCDYL, where expression correlated with progression independently of the linear transcript and the host gene. In summary, our results demonstrate that abundant circRNAs possess multiple biological features, distinguishing them from low-expressed circRNAs and non-circularized exons, and suggest that circRNAs might serve as a new class of prognostic biomarkers in NMIBC. Bladder cancer: Circular RNAs show prognostic biomarker potential Expression levels of non-coding "circular" RNA molecules could be used as a prognostic biomarker for patients with early-stage bladder cancer. A team led by Trine Line Hauge Okholm and Jakob Skou Pedersen from Aarhus University Hospital, Denmark, profiled the expression of these loop-forming, potentially gene-regulating RNAs in biopsied tumor samples from 457 patients with bladder cancer that had not invaded nearby muscle tissue. They identified a suite of 113 circular RNAs that were abundant and differentially expressed between patients with different molecular subtypes of bladder cancer. The researchers also found a smaller set of 13 circular RNAs for which expression levels correlated with disease progression. These non-coding RNA molecules, by indicating likely patient outcomes, could potentially serve as future diagnostic aids to inform treatment strategies and decisions.